MALT1 Inhibition of Oral Carcinoma Cell Invasion and ERK/MAPK Activation. (April 2016) - Chiba, T.; Soeno, Y.; Shirako, Y.; Sudo, H.; Yagishita, H.; Taya, Y.; Kawashiri, S.; Okada, Y.; Imai, K.
The expression of mucosa-associated lymphoid tissue 1 (MALT1) that activates nuclear factor (NF)–κB in lymphocyte lineages is rapidly inactivated in oral carcinoma cells at the invasive front and the patients with worst prognosis. However, its mechanism to accelerate carcinoma progression remains unknown, and this study was carried out to examine the role in invasion. HSC2 oral carcinoma cells stably expressing wild-type MALT1 (wtMALT1) reduced the invasion of basement membrane matrices and collagen gels, and the dominant-negative form (∆MALT1)–expressing cells aggressively invaded into collagen gels. MALT1 decelerated proliferation and migration of cells and downregulated expression of matrix metalloproteinase 2 and 9, which were confirmed by short interfering RNA transfections. Reporter assays and immunoblot analysis showed that MALT1 does not affect the NF-κB pathway but inhibits ERK/MAPK activation. This was confirmed by endogenous MALT1 expression in oral carcinoma cell lines. Orthotopic implantation of ∆MALT1-expressing HSC2 cells in mice grew rapid expansive and invasive tongue tumors in contrast to an absence of tumor formation by wtMALT1-expressing cells. These results demonstrate that MALT1 suppresses oral carcinoma invasion by inhibiting proliferation, migration, and extracellular matrix degradation and that the ERK/MAPK pathway is a target of MALT1 and further suggests a role as a suppressor of carcinoma progression.